Effects of biotic and abiotic factors on forest biomass fractions. Issue 10 (2nd April 2021) - Chen, Renfei; Ran, Jinzhi; Hu, Weigang; Dong, Longwei; Ji, Mingfei; Jia, Xin; Lu, Jingli; Gong, Haiyang; Aqeel, Muhammad; Yao, Shuran; An, Lizhe; He, Jin-Sheng; et al.
Abstract: The extent to which key factors at the global scale influence plant biomass allocation patterns remains unclear. Here, we provide a theory about how biotic and abiotic factors influence plant biomass allocation and evaluate its predictions using a large global database for forested communities. Our analyses confirm theoretical predictions that temperature, precipitation, and plant height and density jointly regulate the quotient of leaf biomass and total biomass, and that they have a much weaker effect on shoot (leaf plus stem) biomass fractions at a global scale. Moreover, biotic factors have larger effects than abiotic factors. Climatic variables act equally on shoot and root growth, and differences in plant body size and age, as well as community species composition, which vary with climate in ways that drown out the variations in biomass fractions. The theory and data presented here provide mechanistic explanations of why climate has little effect on biomass fractions.